2020
DOI: 10.3390/polym12051168
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polyelectrolyte Complex Nanoparticles-PECNs Loaded with Ampicillin by Means of Polyelectrolyte Complexation and Ultra-High Pressure Homogenization (UHPH)

Abstract: This study was focused on synthesizing, characterizing and evaluating the biological potential of Polyelectrolyte Complex Nanoparticles (PECNs) loaded with the antibiotic ampicillin. For this, the PECNs were produced initially by polyelectrolytic complexation (bottom-up method) and subsequently subjected to ultra-high pressure homogenization-UHPH (top-down method). The synthetic polymeric materials corresponding to the sodium salt of poly(maleic acid-alt-octadecene) (PAM-18Na) and the chloride salt of Eudragit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…In inorganic systems, nanoparticles are used with metallic ions, such as silver, gold, and zinc oxide. On the other hand, in organic systems, liposomes and polymer nanoparticles are found [ 31 ]. Similar to hydrogels, nanoparticles have high biocompatibility and biodegradability, and low cytotoxicity.…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In inorganic systems, nanoparticles are used with metallic ions, such as silver, gold, and zinc oxide. On the other hand, in organic systems, liposomes and polymer nanoparticles are found [ 31 ]. Similar to hydrogels, nanoparticles have high biocompatibility and biodegradability, and low cytotoxicity.…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
“…Homopolymers and copolymers of polylactide or polyglycolic acid are frequently used. They are classified according to their architecture into nanospheres, nanocapsules, conjugated polymers, and polyelectrolyte complexes [ 31 ]. Nanoparticles can be used to transport proteins and peptides, whose conjugation generates a synergistic effect that improves the limitations of each one of the materials and achieves uses, such as inhibition of the interactions of pathogenic proteins and high sensitivity in molecular imaging [ 32 , 33 , 34 ].…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
“…The products of the interaction between chemically complementary macromolecules, that is, proton donors and acceptors (IPCs stabilized by a cooperative system of H‐bonds), and oppositely charged polyions (interpolyelectrolyte complexes, IPECs), have been widely investigated for several decades 1‐4 . IPCs and IPECs are products with new properties in comparison with the original polymers, which open up a wide range of possibilities for their application, including systems for controlled drug delivery 5‐13 . It is known that the application of new polymer compounds as excipients in pharmaceutical technology can be associated with a risk of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the third study assessed different polyelectrolyte complex nanoparticles (PECNs) formed between PAM-18Na and EuCl polymers loaded with ampicillin. In this case, a moderate increase in antimicrobial activity was found on each of the resistant S. aureus strains [ 18 ]. Therefore, the results described in the three previous studies suggested that depending on the type of nanoparticle there is a particular antimicrobial effect ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%